The impact of social media marketing on consumer loyalty: a study on Gen X and Y - Oh, Jie Yi (2022)
The objective of this study is to examine the impact of social media marketing (SMM) on consumer loyalty between generation X and Y via customer equity drivers (CED). This study surveyed 200 respondents from Malaysia. The data were analysed via Jamovi and the research hypotheses were examined. The study emerged three significant conclusions. Firstly, the three factors of SMM are interactivity, WOM and personalization. Secondly, SMM have significantly and positively impacted all the drivers of consumer equity. Thirdly, the CED exhibit a significant and positive impact on consumer loyalty between generation X and Y. In addition, this is the first study to define three variables of SMM. The S-O-R model is also introduced in this study as a theoretical bases for connecting SMM to consumer loyalty via CEDs. Besides, this is the first research in Malaysia to look at the impact of SMM on consumer loyalty between generation X and Y using CEDs. On the other hand, this study will assist marketers in enhancing consumer loyalty to generation X and Y by examining SMM.